Local, Controlled Release In Vivo of Vascular Endothelial Growth Factor Within a Subcutaneous Scaffolded Islet Implant Reduces Early Islet Necrosis and Improves Performance of the Graft. Issue 3 (March 2018) - Gebe, John A.; Preisinger, Anton; Gooden, Michel D.; D'Amico, Leonard A.; Vernon, Robert B.
Islet transplantation remains the only alternative to daily insulin therapy for control of type 1 diabetes (T1D) in humans. To avoid the drawbacks of intrahepatic islet transplantation, we are developing a scaffolded islet implant to transplant islets into nonhepatic sites. The implant test bed, sized for mice, consists of a limited (2-mm) thickness, large-pore polymeric sponge scaffold perforated with peripheral cavities that contain islets suspended in a collagen hydrogel. A central cavity in the scaffold holds a 2-mm diameter alginate sphere for controlled release of the angiogenic cytokine vascular endothelial growth factor ( VEGF ). Host microvessels readily penetrate the scaffold and collagen gel to vascularize the islets. Here, we evaluate the performance of the implant in a subcutaneous (SC) graft site. Implants incorporating 500 syngeneic islets reversed streptozotocin-induced diabetes in mice approximately 30 d after SC placement. Controlled release of a modest quantity (20 ng) of VEGF within the implant significantly reduced the time to normoglycemia compared to control implants lacking VEGF. Investigation of underlying causes for this effect revealed that inclusion of 20 ng of VEGF in the implants significantly reduced central necrosis of islets 24 h after grafting and increased implant vascularization (measured 12 d after grafting). Collectively, our results demonstrate (1) that the scaffolded islet implant design can reverse diabetes in SC sites in the absence of prevascularization of the graft site and (2) that relatively low quantities of VEGF, delivered by controlled release within the implant, can be a useful approach to limit islet stress after grafting.